The morphologic and immunohistochemical spectrum of 16 cases of sclerosing stromal tumor of the ovary - Qureshi Asim; Raza Azizunissa; Kayani Naila (Wolters Kluwer Medknow Publications, 2010)
Background: Sex-cord-stromal tumors of the ovary are rare neoplasms and they differ from the common surface epithelial tumors in clinical and imaging features. Patients and Methods: This study was done to evaluate the morphologic and immunohistochemical pattern of 16 cases of sclerosing stromal tumor of the ovary diagnosed at a tertiary care hospital. All patients having sclerosing stromal tumor of the ovary were included with the help of medical records using the SNOMED coding system over 10 year period i.e. 1998 to 2008. Result: Sixteen cases of the stromal tumor of the ovary were diagnosed over this 10 year period; the age range was 23 to 40 years (median age 28). In 7 out of 16 cases, serum CA 125 level was done which was raised as per the available medical records. All of these cases showed unilateral. The gross appearence of all the tumors was similar and all had unilateral involvement. Mucin was negative in all of these cases.